PENGARUH MODEL PEMBELAJARAN SNOWBALL THROWING BERBANTUAN MEDIA VISUAL TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR - Rahma; Astuti; Fadhilaturrahmi; Nurhaswinda; Yenni Fitra Surya (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Snowball Throwing learning model assisted by visual media on the mathematical concept understanding ability of second-grade elementary school students on the Flat Shape material. The population of this study was all second-grade students of SDN 001 Langgini, totaling 30 students. The sample was taken using a purposive sampling technique, namely class II A as the experimental class (15 students) and class II B as the control class (15 students). Data collection techniques in this study used observation, tests, and documentation. The instruments used were student and teacher activity observation sheets, written post-test questions, and photo documentation of learning activities. The experimental class was given treatment using the Snowball Throwing model assisted by visual media, while the control class used conventional learning. The results of the analysis using an independent t-test showed that the average post-test of the experimental class was 85.40, while the control class was 71.00, with a significance value of 0.004 <0.05, which indicated a significant difference between the two classes. Thus, it can be concluded that the Snowball Throwing learning model, supported by visual media, has an impact on elementary school students' mathematical concept understanding.